Impact of Planar and Vertical Organic Field‐Effect Transistors on Flexible Electronics (Adv. Mater. 11/2023). Issue 11 (16th March 2023) - Nawaz, Ali; Merces, Leandro; Ferro, Letícia M. M.; Sonar, Prashant; Bufon, Carlos C. B.
Abstract : Flexible Electronics In article number 2204804, Ali Nawaz, Carlos C. B. Bufon, and co‐workers compare the performance of planar organic transistors the emerging vertical‐transistor technology, outlining the critical device fabrication and material‐design strategies, and discussing their role and function in a wide range of flexible electronics applications. Showcasing research from the Micro Nano Facility (MNF‐SD), Bruno Kessler Foundation (FBK), Trento, Italy, in collaboration with Mackenzie Presbyterian Institute, Chemnitz University of Technology, and Queensland University of Technology.